Removal of Atmospheric Particles in Poor Visibility Outdoor Images - Yaseen Al-Zubaidy; Rosalina Abdul Salam (Institute of Advanced Engineering and Science, 2013)
The visibility of a scene is degraded by weather phenomena such as rain drizzle, fog and haze. The degradation of image scene is due the substantial presence of particles in the atmosphere that scatter and absorb light. As the light spreads from object to the observer, the color and intensity is changed by the atmospheric particles. In this research, we suggest new methods to precisely detect airlight and correctly estimate the atmospheric veil from image that captured in bad weather. The result of suggested methods will be used in scattering atmospheric model to remove atmospheric particles namely, rain drizzle, fog and haze from a single image. Therefore a higher visibility image will be produced. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.2872